THU0161 Increase in Circulating TH17 Cells during Anti-TNF Therapy in Rheumatoid Arthritis Patients is Associated with Improvement in Joint Inflammation. (10th June 2014) - Hull, D.; Abraham, S.; Williams, R.O.; Taylor, P.C.
Abstract : Background: Anti-TNFα agents have revolutionised treatment of rheumatoid arthritis (RA), although a significant proportion of patients respond inadequately. Studies in murine and human arthritis have paradoxically shown that anti-TNF treatment can increase circulating Th17 cells but the relationship of these changes to treatment responses remains unclear. Objectives: To investigate immune correlates of anti-TNF treatment response or failure in RA patients we conducted a longitudinal study using serial clinical, ultrasound and T cells immunological assessments. Methods: 25 RA patients naïve to biological therapy were followed at 4 predetermined protocol visits during the first 12 weeks of anti-TNF treatment (etanercept or adalimumab). Improvement in Disease Activity Score of 28 joints (DAS28) defined treatment responders (n=16) and non-responders (n=9). Changes in synovial thickening and vascularity of 10 metacarpophalangeal joints were quantitatively assessed by 2D high frequency grey scale and power Doppler ultrasound (PDUS) using a digitalised pixel counter. Changes in the frequency of circulating Th17 cells during treatment were evaluated by IL17 ELISpot assay and Flow Cytometry (FACS) of PBMCs. Results: ELISpot analysis demonstrated a significant increase in circulating IL17-producing cells 12 weeks after anti-TNFα initiation (baseline mean ± SD 466±277 vs 12 weeks mean ± SD 759±510 spSFC/10 6, p=0.003). FACS analysis confirmed a significant increase in CD4+IL17+ cells at treatment week 12 (baseline mean ± SD 0.7±0.5% vs 12 weeks mean ± SD 1.1±0.5%; p=0.01). This increase in circulating Th17 cells during anti-TNFα treatment was observed in patients treated with different types of anti-TNFα agents, suggesting this may be a class effect. The increase in circulating Th17 cells during treatment correlated significantly with reduction in synovial vascularity (Spearman rank r= -0.68, p=0.007) and synovial thickening (Spearman rank r= -0.39; p=0.04) as determined by PDUS. Higher numbers of circulating Th17 cells at baseline were associated with poorer anti-TNFα treatment response as defined by ultrasonographic measures. Conclusions: This is the first study to link changes in circulating Th17 cells evaluated by cellular assays with resolution of ultrasonographic features of synovitis during anti-TNF treatment. The findings may reflect redistribution of Th17 cells from inflamed joints during treatment or that TNFa may play a role in the regulation of Th17 cell production, but these two hypotheses are not mutually exclusive. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.1030